2020
DOI: 10.3389/fnut.2020.564379
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Management of Patients With Enterocutaneous Fistulas: Practice and Progression

Abstract: The management of enterocutaneous fistulas (ECF) can be challenging because of massive fluid loss, which can lead to electrolyte imbalance, severe dehydration, malnutrition and sepsis. Nutritional support plays a key role in the management and successful closure of ECF. The principle of nutritional support for patients with ECF should be giving enteral nutrition (EN) priority, supplemented by parenteral nutrition if necessary. Although total parenteral nutrition (TPN) may be indicated, use of enteral feeding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 70 publications
(69 reference statements)
0
19
1
10
Order By: Relevance
“…In this study, the refeeding strategy was performed on the basis of sepsis. As one of the most common critical illnesses in the ICU, sepsis and sepsisassociated nutritional management remain a difficult problem to solve (25). The pathology of lung injury and elevated plasma TNF-α, IL-1β, IL-6, and MPO demonstrated that our sepsis model was well-constructed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the refeeding strategy was performed on the basis of sepsis. As one of the most common critical illnesses in the ICU, sepsis and sepsisassociated nutritional management remain a difficult problem to solve (25). The pathology of lung injury and elevated plasma TNF-α, IL-1β, IL-6, and MPO demonstrated that our sepsis model was well-constructed.…”
Section: Discussionmentioning
confidence: 99%
“…TPN or enteral nutrition is one among the corroborative cares to stop subsequent malnutrition and dyselectrolytemia. 21,22 Gastrointestinal secretions decrease by 30-50 percent in patients getting TPN thus helping in fistula closure.…”
Section: Enteral Versus Parenteral Feedingmentioning
confidence: 99%
“…TPN or enteral nutrition is one among the corroborative cares to stop subsequent malnutrition and dyselectrolytemia. 21 , 22 …”
Section: Enteral Versus Parenteral Feedingmentioning
confidence: 99%
“…An enterocutaneous fistula (ECF) is an abnormal connection between the gastrointestinal tract and the skin or atmosphere (enteroatmospheric fistula [1] [EAF]) .Estimated 75-85% are iatrogenic, occur after an abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways in which ECF has been classified, including by output, etiology, and source [1,2,3]. Most often, a high-output ECF is characterized as one with >500 mL/24 hours, low output <200 mL/24 hours, and a moderate output fistula between 200 and 500 mL/24 hours [1]. Historical reported mortality rates as high as 10-30%.…”
Section: Introductionmentioning
confidence: 99%